Arahan Perencanaan Infrastruktur Kawasan Ekowisata Mangrove Lantebung Kelurahan Bira, Kecamatan Tamalanrea, Kota Makassar - Hasna, Dwi Hartini; Sutopo, Yashinta Kumala Dewi (Pusat Studi Pariwisata Universitas Gadjah Mada, 2025)
The tourism sector is an important role in sustainable economy through the development of quality destinations that supported by infrastructure and digital transformation. One of the destination is Lantebung Mangrove Ecotourism Area in Bira Village, Makassar City. So with this basis, it is necessary to conduct research and evaluation related to the level of infrastructure services that are useful in developing and fulfilling sustainable aspects. This research aims to 1) identify the availability of infrastructure, 2) evaluate the capacity of infrastructure, and 3) formulate the direction of infrastructure availability and capacity. This research was conducted from April to December 2024, located in the Lantebung Mangrove Ecotourism Area, Bira Village, Makassar City. This research is included in qualitative and quantitative descriptive research, using primary data in the form of physical survey results of the area and secondary data in the form of Makassar City RTRW documents and a series of literature studies. The analysis technique esed is descriptive qualitative in the form of contextualizing data from observations and applicable standards, and descriptive quantitative in evaluating infrastructure capacity, and using descriptive qualitative analysis in formulating planning stages. Based on the results of the analysis, it is known that the availability of infrastructure in Lantebung Mangrove Ecotourism Area is quite adequate but needs improvement to support visitor comfort and support the function of the area. Infrastructure directions for the Lantebung Mangrove Ecotourism Area include the development of lodging, viewing towers, photo spots, clean water networks, as well as maintenance of facilities such as toilets and gazebos, are needed for the comfort and safety of visitors, as well as supporting the sustainability of the area.